(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The study was conducted to investigate the effects of application of biosynthesized silver nanoparticles (AgNPs) on the growth and yield performances of rice (Oryza sativa var. Nerica) under salinity conditions in a ferruginous ultisol. AgNPs were biosynthesized following standard procedure using leaves of Hibiscus sabderiffa. Viable rice seeds were sown in soils that were previously moistened with salt solution in 3 concentrations (100, 250 and 400mM). The AgNPs (200ml) was sprayed in five concentrations (5, 10, 15, 20 and 25% v/v) on the test plant for seven weeks. Morphometric parameters such as plant height, root number, leaf length and rice yield parameters were studied. Results showed that salinity significantly (p<0.05) impaired growth and yield parameters of rice at increasing salinity levels, leading to death rice plants exposed to 400mM of salt solution. With the application of AgNPs, significant improvements in growth responses of the plants exposed to salinity; especially at low salt stress and low AgNPs concentration. Plants in ferruginous soils showed minimal increases in measured growth parameters (plant height, root number, leaf length and rice yield) compared to salt stressed plants. Number of roots was observed to be highly significant with the application of AgNPs; however, shelling percentage showed lowest response with the application of AgNPs. There was no significant difference in modal periods taken for complete foliar necrosis as well as complete foliar chlorosis. This paper suggests therefore that minimal application of AgNPs improved growth and yield parameters of rice in minimal saline condition as well.